The Role of Home Industry Tiles in Empowering Human Resources (HR) of the Community of Kamulan Village, Trenggalek Regency - Tamarin Erningtyas; Seli Septiana Pratiwi; Nanda Harda Pratama Meiji (PT. Pena Produktif Kreatif, 2024)
This research analyzes how the roof tile cottage industry contributes to human resource empowerment in Kamulan Village. This research was conducted using a qualitative method. Using empowerment theory by Jim Ife as the theoretical basis of description. Data was collected through purposive sampling, in-depth interviews, observation, and documentation. The analysis was done inductively. The resource persons in this research are stakeholders in Kamulan Village and residents of roof tile craftsmen in Kamulan Village who are experienced in the roof tile industry as many as 8 resource persons. This research describes how the roof tile industry in Kamulan Village plays a role in empowering and absorbing human resources in the village. The results of the research conducted found that the home-based roof tile industry has prospered the lives of residents in the village. Empowerment carried out by residents is carried out well sustainably and actively between owners and workers in work evaluation. However, there are production obstacles with the scarcity of human resources (HR) of residents due to the large number of industries with total employment. The sustainability of the roof tile industry must be considered, especially in the availability of human resources and activating the empowerment of local village human resources. Considering the wider social and environmental impacts, it is strongly recommended that policies and socialization be made that support the growth of the roof tile industry in the future.